2019
DOI: 10.3389/fpsyg.2019.00970
|View full text |Cite
|
Sign up to set email alerts
|

Competing Conversations: An Examination of Competition as Intrateam Interactions

Abstract: Intrateam competition is an inherently social and interactional process, yet it is not often studied as such. Research on competition is mostly limited to studying it as an individual state and assumes that the resulting team outcomes are equivalent across different competition types. Often overlooked in competition research are the means through which competition can lead to constructive outcomes for the team. Constructive competition occurs when the primary motivation is not to win at the expense of others, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
3
0
1
Order By: Relevance
“…Importantly, intragroup competition concerns not only competing for extrinsic rewards but also competing for recognition, for status and power, for displaying self-competence and gaining control of resources, etc. (Abraham, McCusker, & Foti, 2019). There are different ways of operationalizing intragroup competition.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Importantly, intragroup competition concerns not only competing for extrinsic rewards but also competing for recognition, for status and power, for displaying self-competence and gaining control of resources, etc. (Abraham, McCusker, & Foti, 2019). There are different ways of operationalizing intragroup competition.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Although competition and cooperation can have a diverse and considerable effect on team outcomes, measuring the degree to which individuals are engaging in these behaviors can be difficult. To measure competition, researchers often extract features from interactions between individuals (Abraham et al, 2019 ). This process can involve many hours of training research assistants to record and code team interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Successful teams are composed of confident individuals with positive interpersonal relationships (Tjosvold et al, 2003). While meta analysis reveals an overall positive effect of cooperation on interpersonal relationships, compared to competition (Johnson, 2003), other studies have found that competition can improve team satisfaction under certain settings (Tjosvold et al, 2003;Abraham et al, 2019).…”
Section: Introduction Team Competition and Cooperationmentioning
confidence: 99%
“…El conflicto es una situación inevitable cuando se interactúa dentro de un grupo de personas y por tanto debe ser tenido en cuenta cuando se analice el funcionamiento colectivo de cualquier grupo de trabajo (Abraham et al, 2019;Lavoi, 2007). En este sentido, en la rama de la psicología organizacional han sido conscientes de su trascendencia y el estudio de los conflictos cuentan con más de siete décadas de respaldo científico (Barki y Hartwick, 2004; González-Ponce et al, 2018; Paradis et al, 2014).…”
Section: Introductionunclassified